The influence of bystander presence on evaluations of public breastfeeding among adults in the United States - Amy E. Houlihan; Yuliana Zaikman; Allison M. Alford (BMC, 2023)
Abstract Background In general, people tend to support private breastfeeding more than public breastfeeding, and discomfort surrounding public breastfeeding may contribute to sub-optimal rates of breastfeeding in the United States. Few studies have systematically examined situational factors that contribute to (negative) reactions to public breastfeeding. It is unclear whether the physical location or the presence of others is more influential in shaping people's evaluations of public breastfeeding. This study aimed to experimentally investigate the influence of location, bystander presence, bystander gender, and the breastfeeding woman's use of a cover on people's evaluations of breastfeeding images. Method A sample of adults residing in the United States was randomly assigned to view an image of a breastfeeding woman in an experimental study that examined four independent variables: breastfeeding location (public vs. private), bystander presence (present vs. not present), gender of bystander (male vs. female), and use of a cover (cover vs. no cover). Participants then reported their emotional reactions to, perceptions of, and behavioral intentions toward the breastfeeding woman. In addition, participants completed measures of sexism, traditional gender role endorsement, sexual comfort, body gaze, and breastfeeding knowledge and experience. Results Hierarchical regressions revealed no differences between private and public breastfeeding images. Perceptions of the breastfeeding woman were more favorable when she was alone than with others, and when she was covered than when she was not covered. Evaluations tended to be more favorable among participants who scored lower on hostile sexism, higher on benevolent sexism, higher on sexual comfort, and higher on breastfeeding knowledge. Conclusion The presence of bystanders may be more consequential than the physical location in shaping reactions to public breastfeeding. These findings can be applied to improve support for public breastfeeding, which may contribute to higher breastfeeding rates and the associated public health benefits.